A Multiplex High‐Throughput Gene Expression Assay to Simultaneously Detect Disease and Functional Markers in Induced Pluripotent Stem Cell‐Derived Retinal Pigment Epithelium. (29th May 2014) - Ferrer, Marc; Corneo, Barbara; Davis, Janine; Wan, Qin; Miyagishima, Kiyoharu Joshua; King, Rebecca; Maminishkis, Arvydas; Marugan, Juan; Sharma, Ruchi; Shure, Michael; Temple, Sally; Miller, Sheldon; et al.
Abstract : This study used a multiplex high‐throughput gene expression assay that simultaneously detects endogenous expression of multiple developmental, functional, and disease markers in induced pluripotent stem (iPS) cell‐derived retinal pigment epithelium (RPE). This assay provides the basis to screen for compounds that improve RPE function and maturation and target disease pathways, thus providing the basis for effective treatments of several retinal degenerative diseases. Abstract : There is continuing interest in the development of lineage‐specific cells from induced pluripotent stem (iPS) cells for use in cell therapies and drug discovery. Although in most cases differentiated cells show features of the desired lineage, they retain fetal gene expression and do not fully mature into "adult‐like" cells. Such cells may not serve as an effective therapy because, once implanted, immature cells pose the risk of uncontrolled growth. Therefore, there is a need to optimize lineage‐specific stem cell differentiation protocols to produce cells that no longer express fetal genes and have attained "adult‐like" phenotypes. Toward that goal, it is critical to develop assays that simultaneously measure cell function and disease markers in high‐throughput format. Here, we use a multiplex high‐throughput gene expression assay that simultaneously detects endogenous expression of multiple developmental, functional, and disease markers in iPS cell‐derived retinal pigment epithelium (RPE). We optimized protocols to differentiate iPS cell‐derived RPE that was then grown in 96‐ and 384‐well plates. As a proof of principle, we demonstrate differential expression of eight genes in iPS cells, iPS cell‐derived RPE at two different differentiation stages, and primary human RPE using this multiplex assay. The data obtained from the multiplex gene expression assay are significantly correlated with standard quantitative reverse transcription‐polymerase chain reaction‐based measurements, confirming the ability of this high‐throughput assay to measure relevant gene expression changes. This assay provides the basis to screen for compounds that improve RPE function and maturation and target disease pathways, thus providing the basis for effective treatments of several retinal degenerative diseases.